Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I know how to prove whether or not vectors are linearly independent, but can't apply the same thing to matrices it seems. Given three 2x2 matrices, for example:

$$A = \begin {bmatrix} -1&1 \\\\ -1&1 \ \end{bmatrix}$$ $$B = \begin {bmatrix} 1&1 \\\\ -1&-1 \ \end{bmatrix}$$ $$C = \begin {bmatrix} -1&1 \\\\ 1&-1 \ \end{bmatrix}$$

I want to test whether or not these are linearly dependent. So with vectors I would do something like:

$$ c_1A + c_2B + c_3C = 0$$

Where the cs are some scalar constants, and prove that the only solution of that is when $$c_1 + c_2 + c_3 = 0$$

So how do I go about solving this:

$$ c_1 \begin {bmatrix} -1&1 \\\\ -1&1 \ \end{bmatrix} + c_2 \begin {bmatrix} 1&1 \\\\ -1&-1 \ \end{bmatrix} + c_3 \begin {bmatrix} -1&1 \\\\ 1&-1 \ \end{bmatrix} = 0$$

Or I am going about this completely the wrong way?

Any help would be hugely appreciated.

share|improve this question

2 Answers 2

up vote 5 down vote accepted

You're going about it exactly the right way. EDIT: As David Mitra points out, you have to prove that $c_1=c_2=c_3=0$, not just that $c_1+c_2+c_3=0$.

In fact, you can just think of the matrices as being vectors of length 4: $$\begin{pmatrix}a & b \\ c& d\end{pmatrix}\mapsto (a,b,c,d)$$ and use your knowledge about the linear independence of vectors.

share|improve this answer
    
So I can rewrite the matrices like this: $$ A = (-1, 1, -1, 1) $$ and so on for the others. How does that simplify the problem? I will get: $$ c_1(-1, 1, -1, 1) + c_2(1, 1, -1, -1) + c_3(-1, 1, 1, -1) = 0 $$ Will that give me four equations? –  MadScone Dec 9 '11 at 16:52
    
Well, it doesn't simplify the problem, but you said you know how to check whether vectors were linearly independent, so I was explaining how to think of it in terms of what you're already familiar with. So yes, you get the four equations $$\begin{align*}-c_1+c_2-c_3&=0\\ c_1+c_2+c_3&=0\\ -c_1-c_2+c_3&=0\\ c_1-c_2-c_3&=0\end{align*}$$ –  Zev Chonoles Dec 9 '11 at 17:56
    
Ok thanks, that's all I really needed to know I suppose. I solved the question like this: $$ \operatorname{rref}\left[\begin{array}{ccc|c} -1&1&-1&0 \\ 1&1&1&0 \\ -1&-1&1&0 \\ 1&-1&-1&0 \end{array}\right] = \left[\begin{array}{ccc|c} 1&0&0&0 \\ 0&1&0&0 \\ 0&0&1&0 \\ 0&0&0&0 \end{array}\right] $$ so the matrices are linearly independent. Assuming that's right, my question has been answered. –  MadScone Dec 9 '11 at 19:41
    
@MadScone: I've fixed up the formatting on your comment above. And that looks right to me :) –  Zev Chonoles Dec 9 '11 at 19:58

It's perfectly fine (except that, if you want to prove independence, you need to show $c_1=c_2=c_3=0$, not that their sum is 0). Next, do the matrix arithmetic on the left hand side:

$$ c_1 \begin {bmatrix} -1&1 \\\\ -1&1 \ \end{bmatrix} + c_2 \begin {bmatrix} 1&1 \\\\ -1&-1 \ \end{bmatrix} + c_3 \begin {bmatrix} -1&1 \\\\ 1&-1 \ \end{bmatrix} = \begin {bmatrix} -c_1+c_2-c_3&c_1+c_2+c_3\\\\ -c_1-c_2+c_3 & c_1-c_2-c_3 \ \end{bmatrix} ={\bf 0}. $$

Since a matrix is the zero matrix if and only if each of its components is 0, you get the system of equations $$\eqalign{ -c_1+c_2-c_3&=0\cr c_1+c_2+c_3&=0 \cr -c_1-c_2+c_3&=0 \cr c_1-c_2-c_3&=0 } $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.